Magnetic resonance spectroscopy biomarkers in term perinatal asphyxial encephalopathy: from neuropathological correlates to future clinical applications. - Robertson,NJ; Thayyil,S; Cady,EB; Raivich,G (Curr Pediatr Rev, 2014)
Neonatal brain injury remains a devastating condition, with poor outcomes despite the institution of an effective neuroprotective strategy of therapeutic hypothermia. There is an urgent need to develop additional neuroprotective strategies and to tailor our clinical predictive ability for families and their infants. Such goals could be more readily achieved if reliable early clinical indicators or biomarkers existed. This review will explore the relation between magnetic resonance (MR) imaging biomarkers and the degree of brain pathology observed in our translational piglet model of perinatal asphyxia. We also suggest biomarker relevance at a cellular level. The review will describe the development needed to optimize and simplify the use of biomarkers to speed up future trials of neuroprotection.